외과의사 관점에서 외상전문의의 필요성과 과제 - 이국종 (Daehan oe'sang haghoeji, 2008)
When man first walked on this planet, injury must have been a close encounter of the first kind. The outbreak of World War I, during a period of rapid scientific growth in the basic sciences, demonstrated the need to develop better methods of care for the wounded, methods that were later applicable to the civilian population. Trauma is a multisystem disease and, as such, benefits from almost any advance in medical science. As we learn more about the physiology and the biochemistry of various organ systems, we can provide better management for trauma victims. Improved imaging techniques, better appreciation of physiologic tolerance, and increased understanding of the side effects of specific surgical procedures have combined to reduce operative intervention as a component of trauma patient care. On the other hand, because of this rapid development of medical science, only a few doctors still have the ability to treat multisystem injuries because almost doctor has his or her specialty, which means a doctor tends to see only patients with diagnoses in the doctor’s specialty. Trauma Surgeons are physicians who have completed the typical general surgery residency and who usually continue with a one to two year fellowship leading to additional board certification in Surgical Critical Care. It is important to note that trauma surgeons do not need to do all kinds of operations, such as neurosurgery and orthopedic surgery. Trauma surgeons are not only a surgeon but also general medical practitioners who are very good at critical care and coordination of patient. In order to achieve the best patient outcomes, trauma surgeons should be involved in prehospital Emergency Medical Services, the Trauma Resuscitation Room, the Operating Room, the Surgical Intensive Care and Trauma Unit, the Trauma Ward, the Rehabilitation Department, and the Trauma Outpatient Clinic. In conclusion, according to worldwide experience and research, the trauma surgeon is the key factor in the trauma care system, so the trauma surgeon should receive strong support to accomplish his or her role successfully. (J Korean Soc Traumatol 2008;21:1-7) KCI Citation Count: 8